In pursuit of financial well-being: the effects of financial literacy, financial behaviour and financial stress on employees in Labuan / Zaiton Osman, Erni Marlina Madzlan and Phang Ing - Osman, Zaiton; Madzlan, Erni Marlina; Ing, Phang (Universiti Teknologi MARA Cawangan Sarawak, 2018)
The exposure to a plethora of choices and relatively complex financial products has intensified the need for financial knowledge adequacy in order to acquire the skills needed to make sound financial decisions. The study aimed to examine the effects of financial literacy and financial behaviour on respondents’ financial well-being and to assess the role of financial stress in mediating these relationships. Using a web-based online survey approach, a total of 213 employees in the government and private sectors in the Federal Territory of Labuan responded to the self-administered questionnaire via convenience sampling technique. All data were analyzed using Partial Least Square (PLS) version 3.0. This study found significant relationships between financial literacy, financial stress, and financial well-being. However, there was no significant correlation between financial behaviour and financial wellbeing. Subsequently, financial stress proved to have no mediating effect on predicting employee’s financial well-being in FT Labuan.